Enhancing Economics Learning Outcomes through Problem-Based Learning Integrated with Educaplay: Evidence from Indonesian Senior High School Students - Nuriza Safira; Mira Chairani; Intan Zuhra (LPPM STKIP Kusuma Negara, 2026)
To address poor student performance caused by conventional teacher-centric lessons and a lack of interactive tools, this study examined the efficacy of the Problem-Based Learning (PBL) model integrated with Educaplay media on eleventh-grade economics students at SMA Negeri 1 Makmur. PBL was used to build problem-solving and critical thinking skills, while Educaplay targeted student motivation through gamification. Using a quantitative quasi-experimental approach with a Nonequivalent Control Group Design, 60 students were split into experimental and control groups. Pretest and posttest data from 20 multiple-choice items were analyzed using IBM SPSS Statistics version 27 to test normality, homogeneity, and hypotheses. The results revealed a 2-tailed significance of 0.000 () and a t-value of 19.174 (exceeding the t-table of 1.671), leading to the rejection of and acceptance of . The study concludes that the Educaplay-assisted PBL model significantly enhances economics learning outcomes.